2008 IEEE 2nd International Power and Energy Conference 2008
DOI: 10.1109/pecon.2008.4762685
|View full text |Cite
|
Sign up to set email alerts
|

Optimal location of FACTS devices for damping oscillations using residue factor

Abstract: This paper proposes a residue method to find the optimal location of the FACTS controllers to damp out the inter-area mode of oscillations. Three types of FACTS controllers have been considered, which include static var compensator, thyristor-controlled series compensator and unified power flow controller. The residue method is base on the facts that it is the product of the mode's observability and controllability index of FACTS controllers to the critical mode. The placements of FACTS controllers have been o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…A new approach based on sensitivity indices has been used for the optimal placement of various types of FACTS controllers such as TCSC, TCPAR and SVC in order to minimize total system reactive power loss and hence maximizing the static voltage stability in [201]. Magaji and Mustafa et al [43] has been suggested a residue factor approach for optimal location of FACTS devices for damping oscillations of power systems. An opening of unused potentials of transmission system due to environmental, right-of-way and cost problems is a major concern of power transmission network expansion planners and policy makers.…”
Section: Sensitivity Based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new approach based on sensitivity indices has been used for the optimal placement of various types of FACTS controllers such as TCSC, TCPAR and SVC in order to minimize total system reactive power loss and hence maximizing the static voltage stability in [201]. Magaji and Mustafa et al [43] has been suggested a residue factor approach for optimal location of FACTS devices for damping oscillations of power systems. An opening of unused potentials of transmission system due to environmental, right-of-way and cost problems is a major concern of power transmission network expansion planners and policy makers.…”
Section: Sensitivity Based Methodsmentioning
confidence: 99%
“…References [3]- [5], classify three broad categories such as a sensitivity based methods, optimization based method, and artificial intelligence based techniques for placement of FACTS controllers from different operating conditions viewpoint in multi-machine power systems. The various sensitivity based methods have been proposed in literatures includes eigen-value analysis based methods [6]- [12], modal analysis techniques [13]- [15], index methods [16]- [23], residue-based methods [24]- [25], [43], [168], [169], and other sensitivity based methods [26]- [37], [53], [157]- [167], [201].…”
Section: Introductionmentioning
confidence: 99%
“…Fig.1 (b) represents the linearized block diagram of a SMIB system with STATCOM. Linearized model was considered in order to study the low frequency transient stability oscillations with a smaller variation of load [9], [11].…”
Section: System Under Studymentioning
confidence: 99%
“…Contrasting to the heuristic methods, some authors proposed the analytical methods. For example, Sadikovic et al, Magaji et al [23,24] have proposed the residue factor method to damp inter-area mode of oscillations. Kunnar et al [25] have utilized the modal controllability index to dampen inter-area oscillations.…”
Section: Introductionmentioning
confidence: 99%